The ethical sense and its end authenticity - De la Cruz-Campos, Miguel A. (2021)
The research line of this work is: Educational epistemology, and as a sub-line of research: Histories and educational systems. Philosophy and education. This research has focused on the development of two capacities, the ethical sense, which consists of having the ability to reason and argue; and the authenticity that is the result of the previous one, but is characterized by acting according to listening to one's own being. The objective of this research has been to analyze if the students of the master's degree have knowledge of the ethical sense and authenticity. The methodology of this work belongs to the qualitative approach, of the grounded theory type; the techniques with which the information was collected was the questionnaire with open questions and a study diary. The results of the study determined that there is a direct relationship between the ethical sense and authenticity, and when confronted it could be seen that the students are between: the first level is 16 and the second level is 6. Therefore, it is determined that students are unaware of both abilities.